Application of Lean Six Sigma for Improve Productivity at The Mechanical Plant. A Case Study - Ly Duc, Minh; Thu, Minh Nguyen (Manufacturing Technology Journal, 2022)
This study focuses on performing the analysis of manipulator operations on the machining line of precision mechanical products using the Human-Machine correlation analysis tool through images collected from the camera, wasteful operations incurred in machining according to Lean Six Sigma (LSS) standards to control fluctuations in the machining line, improving the overall productivity of the line (OEE). Specifically, contributing to improving productivity, quality, and competitiveness of the company in the market, create a good product image for consumers. This paper proposes a 7-step quality control (QC) cycle improvement model, called 10 step QC cycle. In step 5, use Man - Machine correlation analysis tool from video images to identify wasteful activities. In step 6, we propose a Direct Numerical Control (DNC) model to call the machining program for MC machines using a barcode system and a computer vision model for human identification at each processing line according to a controlled fixed layout. The right people have been trained enough to operate the line; the specific result is eliminating the occurrence of accidents in processing from 7 cases to none. A model of a product dimensioning system implemented for fully automated product quality control combined with redesigned machining jig with a vapor sensor system eliminating the reliance on human manipulation Specifically, the result from this improvement activity is the increase in productivity from 115 products per 8 hours to 155 products per 8 hours and the handling time has decreased from 1.3 hours per day to 0.36 hours per day (reduce 0.94 hours per day). The Partial Least Squares Structural Equation Modeling (PLS-SEM) is used to analyze the results of the survey of employees' opinions about the usefulness, convenience, and technical factors after the operation. The results from improvement activities show that user loyalty is highly appreciated in terms of usefulness and convenience. However, in terms of technical factors, it is still necessary to improve the quality of the information network system, the barcode scanning system and the quality of barcodes in the oil environment
Keywords: Productivity improvement; QC Story; DMAIC; PLS-SEM; Continuous improvement